PERAN TAX RISK DALAM MEMODERASI PENGARUH TAX SAVING TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - David Adar Hazael; Nur Cahyonowati (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of tax saving on firm value by considering the moderating role of tax risk in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. A quantitative approach was purposive sampling, resulting 200 firm-year observations during the study period. The data were analyzed using multiple linear regression with a moderated regression analysis (MRA) approach, supoorted by SPSS software. The results show that tax saving has a positive and significant effect on firm value. This indicates that efficient and compliant tax-saving strategies send positive signals to investors and enchance the company’s market valuation. However, tax risk does not significantly moderate the relationship between tax saving and firm value. This finding suggest that tax risk is not yet fully considered by investors in their valuation of the firm, possibly due to the limited disclosure of tax risk information in financial reports.Overall, the study supports the signaling theory and managerial efficiency theory, where legitimate tax saving is viewed positively by the market. Conversely, tax risk has not become a key factor in investor assessment. These findings are important for company management, investors, and regulators in formulating tax strategies, improvising fiscal transparency, and developing corporate governance policies that support long-term value sustainability.